Optimalisasi Strategi Pemasaran Digital sebagai Upaya Peningkatan Omset bagi UMKM Batik di Era Society 5.0 - Wenti Ayu Sunarjo; Amalia Ilmiani; Nadia Putri Kamila (FEB Universitas Pekalongan, 2023)
MSMEs have become one of the forces with a massive impact that has been supporting the country's economy which is overcoming obstacles in the new normal era. The main problem for MSMEs from time to time is continuity, one of which is the decrease in turnover which results in MSMEs not being able to survive long. These problems can be overcome by optimizing the role of innovation in promotion and marketing which is closely related to increasing turnover. One of the strategies that can be carried out is through the promotion and marketing of online media and marketplaces as online shopping marketing media which are currently the center of attention of all people in the world. In line with the objective of the activity, namely to overcome the problems of MSMEs by providing assistance in optimizing marketing strategies so that they have an impact on the economic stability of MSMEs, especially in the field of batik in Indonesia.